Studi Analisis Fasilitas Jembatan Penyeberangan Orang di Kota Tarakan - Daud Nawir; Rusmiyanti Rusmiyanti (Borneo Engineering : Jurnal Teknik Sipil, 2019)
The provision of crossing facilities which is a Pedestrians Bridge In Tarakan city, was first built.This research was to aim of knowing the crossing facilities that are in accordance with the location conditions of the research study, both technically and in a special standard design, knowing the level of performance of the Pedestrians Bridge Facility for pedestrians. Data analysis of the number of vehicle volumes (V) is 5126 vehicles / hour and pedestrian volume (P) is 66 people / hour using the PV 2 formula 1728882386.2. Through Determination of crossing facilities on Yos Sudarso, in front of Grand Tarakan Mall, only requires Pelican with a protector or Pelican Crossing along with a waiting stall that has the criteria for the number P = 50 - 1100 people / hour, V 700 vehicles / hour and PV2 2x10 8. For the bridge design, found on the standard for building stair height, did not meet the standards, which was 1.35 meters, while the height of the backrest in the field was 1.15 - 1.20 meters. The level of The Pedestrian Bridge use was 68.77% and could be stated as beneficial. The results of the questionnaire were obtained on the Cartesian diagram in quadrant 1, which is the main priorities that must be improved in the Pedestiran Bridge services are the ease of access for persons with disabilities and the hygiene care of the Pedestrian Bridge’s facilities.